Pelatihan Packaging Teh Herbal dari Bahan Alam Desa Namo Sialang Kabupaten Langkat Sumatera Utara - Julianti, Elisa; Irni, Julaili; Zuliyanti, Ameilia; Batubara, Ridwanti; Pinem, Laura Juita; Pratomo, Bayu (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2024)
This community service program aims to increase the knowledge and skills of Women in Namo Sialang Village, packaging herbal tea products produced by processing natural ingredients like rose, tawar and sembur (made from special spices and herbs from the community). The method for implementing this service used participatory training with activities including socialization and assistance with product packaging. The number of participants involved was 20, consisting of a Women Group named